Individual and Collective Self-Identification as Indigenous in the European Arctic:International Legal Perspectives - Kirchner, Stefan (2019)
Who is indigenous is a question which is often difficult to answer from the perspective of non-indigenous law. Lovelace v. Canada is one of the key cases of indigenous rights law. It forms an important precedent but it does not establish an unlimited subjective right to be indigenous within the framework of the ICCPR. The decision in Lovelace v. Canada cannot be construed as requiring states which are parties to the ICCPR to allow anybody to claim indigenous identity without the consent of the indigenous people in question. ILO 169 strengthens the position of indigenous peoples in this regard. Self- identification has multiple dimensions: collective self-identification as indigenous, individual self-identification as indigenous, and collective identification of the self through the identification of an individual as indigenous. Only indigenous peoples can decide who is a member. This decision is a sovereign right of the collective.